“Justitia Semper Reformanda Est”: A Philosophical Reflection on the Law and Its Change - Ratuanak, Andreas M. D. (Dialogia Iuridica, 2023)
The theme of the law and its changes is still being discussed in the academic community. The fact that law requires social society as its habitat makes it difficult to maintain the status quo. The social community always changes according to the era and place where it makes the laws also voluntarily or is forced to make adjustments to its habitat. The article will discuss how the law cannot always be consistent because it is influenced by the social conditions in which the law lives, how the process of change occurs, and what factors influence the inconsistency of the law, in a philosophical reflection. By using a literature research approach, this research aims to explore two main questions, namely: does law change society or vice versa? and; what factors are most influential in encouraging legal change? This study reflects that jurists from various views seem to agree on one thing, that the law is changing and they only provide different criteria and procedures. This reflection culminates with a statement that the law is always changing, and it reforms itself all the time.